Life history characteristics of the western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), under fluctuating conditions of temperature or relative humidity - Park, Young-gyun; Lee, Joon-Ho (Journal of Asia-Pacific entomology, 2020)
[Display omitted] •F. occidentalis was significantly affected by fluctuating temperature or humidity.•The r was higher under high fluctuation condition of relative humidity.•The r was lower under high fluctuation conditions of temperature. Frankliniella occidentalis (Pergande) is a major insect pest of greenhouse crops such as leaf vegetables, flowers and vegetable fruits worldwide. The life history characteristics of F. occidentalis were investigated at control temperature and humidity (27.3 ± 0.54 °C, 79.9 ± 2.79% RH) (mean ± SD), a 10 °C-range fluctuation in temperature (27.1 ± 5.28 °C, 81.5 ± 4.03% RH), a 20 °C-range fluctuation in temperature (26.5 ± 10.09 °C, 80.4 ± 5.76% RH), a 20%-range fluctuation in humidity (26.8 ± 0.37 °C, 80.7 ± 9.55% RH) and a 30%-range fluctuation in humidity (27.3 ± 0.41 °C, 76.3 ± 15.28% RH). Overall, the life history traits of F. occidentalis were more negatively affected by fluctuating environmental conditions. The impact of temperature fluctuation was more severe than that of humidity fluctuation. Additionally, the degree of impact increased as the fluctuation range of the temperature increased, while the reverse trend was observed with humidity fluctuations. With the 20 °C-range fluctuation in temperature, F. occidentalis died at the 1st instar larval stage. The offspring’s sex ratio was significantly higher at the 20%- and 30%-range fluctuations in humidity (0.47 and 0.49, respectively) compared to the control (0.35) and at the 10 °C-range fluctuation in temperature (0.33). From the fertility life table analysis, the intrinsic rate of increase (r) was higher at the 30%-range fluctuation in humidity and control conditions as 0.218 and 0.205, respectively. At the 10 °C-range fluctuation in temperature conditions, r was significantly lower as 0.169. High fluctuations in temperature and low fluctuations in humidity appear to be the best conditions for controlling F. occidentalis populations in greenhouses.